The development of waste to energy in Semarang, Indonesia. Issue 1 (November 2021) - Hadi, S P; Prabawani, B; Hamdani, R S
Abstract: The volume of solid waste in Semarang City reached 1, 300 tons per day consisting of 65 percent organic and 35 percent inorganic waste. 77.64 percent of waste was transported and disposed at Jatibarang landfill, 17.65 percent was managed by waste Bank and by temporary landfills (TPS) and 4.71 percent waste remain unmanaged. Jatibarang landfill is predicted to be exceeded its carrying capacity in 2021. To deal with this problem, through a public private partnership scheme, a PLTSa (waste to energy) has been developed. PLTSa would manage 70 percent of waste and produce 20 MW electricity sold to the State Electricity Company (PLN). The government of Semarang City must pay a tipping fee of 780, 555 IDR per ton to the PLTSa Management. This paper analyses the development of PLTSa by comparing with another similar project. The research method was descriptive analysis, relied on secondary data, webinars, and informal interviews with relevant persons. This study found that waste to energy project will create dependency on the city government financially and operationally. To create sustainable waste management, it is recommended to utilize appropriated technology enabling the city government to operate by themselves and enjoy the benefit of electricity resulted from the process.